Nonlinear Wave‐Particle Interaction: Implications for Newborn Planetary and Backstreaming Proton Velocity Distribution Functions. Issue 2 (1st February 2018) - Romanelli, N.; Mazelle, C.; Meziane, K.
Abstract: Seen from the solar wind (SW) reference frame, the presence of newborn planetary protons upstream from the Martian and Venusian bow shocks and SW protons reflected from each of them constitutes two sources of nonthermal proton populations. In both cases, the resulting proton velocity distribution function is highly unstable and capable of giving rise to ultralow frequency quasi‐monochromatic electromagnetic plasma waves. When these instabilities take place, the resulting nonlinear waves are convected by the SW and interact with nonthermal protons located downstream from the wave generation region (upstream from the bow shock), playing a predominant role in their dynamics. To improve our understanding of these phenomena, we study the interaction between a charged particle and a large‐amplitude monochromatic circularly polarized electromagnetic wave propagating parallel to a background magnetic field, from first principles. We determine the number of fix points in velocity space, their stability, and their dependence on different wave‐particle parameters. Particularly, we determine the temporal evolution of a charged particle in the pitch angle‐gyrophase velocity plane under nominal conditions expected for backstreaming protons in planetary foreshocks and for newborn planetary protons in the upstream regions of Venus and Mars. In addition, the inclusion of wave ellipticity effects provides an explanation for pitch angle distributions of suprathermal protons observed at the Earth's foreshock, reported in previous studies. These analyses constitute a mean to evaluate if nonthermal proton velocity distribution functions observed at these plasma environments present signatures that can be understood in terms of nonlinear wave‐particle processes. Key Points: Nonlinear particle trapping in velocity space by right‐handed parallel propagating electromagnetic waves is studied in detail We determine the theoretical pitch angle centroids for nominal conditions in the upstream region of Mars and Venus and planetary foreshocks Similarities and differences in the particle's dynamics when forced by a circularly and elliptically polarized wave are analyzed